Analysis Validation of Quantum Physics Learning Devices using Blended Learning Models to Improve Critical Thinking and Generic Science Skills of Students - Aris Doyan; Susilawati Susilawati; Saprizal Hadisaputra; Lalu Muliyadi (Postgraduate, University of Mataram, 2022)
This study aims to develop a quantum physics learning device with a blended learning model to improve the critical thinking and generic science skills of students. The learning device is made with a 4D development model which includes four steps, namely: define, design, develop, and disseminate. The learning tools developed to consist of semester program plans (SPP), student activity sheets (SAS), quantum physics teaching materials, instruments to measure critical thinking skills, and generic science skills of students. The validity results show that the quantum physics learning device with the blended learning model has an average value of more than 4.20. This shows that the learning tools are very feasible to improve the critical thinking and generic science skills of students.